O processo de construção do sujeito-artista Maxwell Alexandre no contexto complexo da política contemporânea - Carlin, Mariana Henriques Duarte (2023)
The present research starts from the observation of action standard´s recurrence in the use of the social network Instagram by visual artists, which detonated discomforts and stimulate a reflection on the subjectivity of the creative agent, eminently supported by the theories of Vincent Colapietro, Judith Butler and Vilém Flusser. The object of the research comes from the mapping of the creation process disclosed in the social network profile of the artist Maxwell Alexandre, in order to elucidate the complex hypothesis that his work contemplates from the canvases exposed in galleries and museums, passing through the performances and events publicized by the Instagram and content curation itself. The selection of this artist is justified by the fact that his work circulates both in the traditional arts circuit and in digital networks, which allows identifying redundancies, ambiguities and disruptions that would reveal the originality of his work. Understanding the creation process as a collective exercise, influenced and shaped by cultural references, the political environment, restrictions and needs, elucidating what Vincent Colapietro theorized about the decentering of the subject, is the starting point for the development of the research . The study will be conducted based on the principle that theoretical reflections on networks require an approach based on this relational paradigm. The ways of apprehending a thought in a network must necessarily also be in a network, that is, in the constitution of an organic and relational theoretical body (Cecilia A. Salles). In this sense, it starts with the discussion on the three theoretical axes that guide the project: complexity (Edgar Morin, E. de Assis Carvalho, M.J.E. Vasconcellos), semiotics (Charles S. Peirce and Vincent Colapietro) and network (Pierre Musso). With this, the concept of creation will be taken as a network under construction, with a focus on hypermedia production, which, while breaking the physical, territorial, elitist and marketing limitations of the traditional visual arts circuit, subjects it to its new impositions, often imperceptible to the opaque look at which the cultural perspective of neoliberalism directs us. At the same time that it offers this broad spectrum of action to the creative agent, social networks use tools to control human behavior that can be understood as structures typical of the network of molecular powers that are incorporated throughout culture and act on bodies, as an evident updating of the Biopolitics theorized by Michel Foucault. The possibility of refusing mimetic standards and the permeability for the usurpation of the digital tools themselves, causing disruption and estrangement, can, however, open the semiotic circuits to the event and the consequent outbreak of a new policy